PENGARUH KOMPETENSI APARATUR DESA, MORALITAS INDIVIDU DAN BUDAYA ORGANISASI TERHADAP PENCEGAHAN KECURANGAN (FRAUD) DALAM PENGELOLAAN KEUANGANDESA: STUDI EMPIRIS PADA PEMERINTAH DESA SE-KOTA DENPASAR - Indah Aprilia, Kadek Wiwin (Hita Akuntansi dan Keuangan, 2021)
Fraud prevention s an effort that can be done to suppress or prevent the factors that cause fraud. In preventink the occurrence of the fraud factor, fraud prevention can be used as an effort to minimise the occurrence of factor that cause fraud. The population in this study were all village apparatuses in the village in Denpasar cty. The respondents used were 80 people consisting of the Village Head, Village Secretary and Head Of Finance. The method of determining the simple using purposive sampling technique. From the results of this study the competence of village officials, individual morality and organizational culture have a positive effect on the prevention of fraud in village financial management at village governments throughout Denpasar.